Multi-omics analysis of flavor differences in pectoral muscles between Wuqin 10 duck and Cherry valley duck - Ping Gong; Shengqiang Ye; Xing Chen; Lixia Wang; Yunguo Qian; Mingli Zhai; Yu Yang (Frontiers in Molecular Biosciences)
This study aimed to explore the impact of breeds on the lipid composition and flavor substances in duck pectoral muscles. In this study, 63-day-old Wuqin 10 ducks (WQ) and Cherry Valley ducks (CV) were selected as the research objects. The pectoral muscle tissues were collected. The composition of volatile flavor substances in pectoral muscles was detected by using headspace solid-phase microextraction combined with comprehensive two-dimensional gas chromatography-time-of-flight mass spectrometry. The lipid composition of pectoral muscles was determined by liquid chromatography-mass spectrometry, and the differentially expressed genes in duck pectoral muscles were determined by a high-throughput sequencer. Through integrated analysis, the main substances and main genes that affect the flavor of ducks were identified. The results showed that the detection results of flavor substances indicated that eight differential volatile compounds were screened out in the comparison between WQ ducks and CV ducks, namely, 4(1H)-Pyridinone, 2, 3-dihydro-1-methyl-, 1-Octen-3-ol, Hexanoic acid, trans-4-tert-butylcycloheptanol, 1-Octanol, 2, 4-Decadienal, (E, E)-, N, N′-Diacetylethylenediamine, Pyrimidine, 4-butyl-3, 4-dihydro-5-methyl-. The differential volatile compounds were mainly manifested in hydrocarbons, aldehydes and ketones, esters. A total of 86 differential lipids were screened out in the comparison between WQ ducks and CV ducks. Among them, the lipid differences between WQ and CV ducks were mainly in triglycerides (TG), phosphatidylcholines (PC) and glycerophospholipids (PE). A total of 500 differentially expressed genes were screened out in the comparison between WQ ducks and CV ducks. These differentially expressed genes were mainly involved in pathways such as glycerolipid metabolism, fatty acid degradation, and regulation of lipolysis in adipocytes. In summary, this study screened and determined that eight volatile organic compounds were the key aroma substances in the pectoral muscles of the two groups of ducks, and 86 differential lipids could distinguish the pectoral muscles of the two groups of ducks. Triglycerides (TG), phosphatidylcholines (PC) and glycerophospholipids (PE) played a crucial role in the formation of volatile compounds in pectoral muscles. The differentially expressed genes TPP1 and PNPLA2 might play an important role in the generation of flavor substances in duck pectoral muscle tissues.